Bidirectional pathogenesis between non-tuberculous mycobacteria and bronchiectasis: clinical insights, diagnostic challenges and future directions—Perspectives from South Asia - Singh, Amresh Kumar; Singh, Sneha; Singh, Nandini; Gaur, Priyanka; Mishra, Ashwini Kumar; Singh, Raj Kishore; Kumar, Sushil (Frontiers in Tuberculosis, 2026)
Non-tuberculous mycobacteria (NTM) are environmental opportunistic pathogens causing chronic pulmonary disease. NTM pulmonary disease (NTM-PD) and bronchiectasis exhibit a bidirectional pathogenic relationship that is particularly under recognized in South Asian regions with high tuberculosis (TB) burden. This review article covers most of the current evidence on the epidemiology, clinical spectrum, pathogenesis, therapeutic advances of NTM-associated bronchiectasis. A well-structured literature search was conducted across PubMed, Web of Science, Scopus, and Google Scholar for articles published within from 2008 to 2025. These studies were specifically focused on NTM -associated bronchiectasis for host pathogen interactions, diagnostic strategies, and treatment outcomes. The prevalence of NTM related bronchiectasis especially with species like Mycobacterium avium complex and Mycobacterium abscessus which were more frequent pathogens all over the world. Its diagnostic dilemma with TB remains widespread due to limited lab capacity and lack of exact species identification, which leads to late or wrong diagnosis. Integration of molecular diagnostic tools, inclusion of NTM within national TB programs, and establishment of regional reference laboratories are essential to improve early detection, targeted treatment, and disease surveillance for bronchiectasis.